(untitled) (Tanzania Journal for Population studies and Development, 2010)
This study was conducted in Korogwe district involving 100 women farmers randomly selected from four villages. Household data was collected using a structured questionnaire, and supplemented by interviews for key informants and Focus Group Discussions (FGD). The Statistical Package for Social Sciences (SPSS) software was used to analyse the data. The findings showed that education, age, extension services, and mass media determine the access and utilization of agricultural information. Furthermore, low production was due to lack of extension services, low education of the respondents, inability to access credit andunawareness of sources of information. Moreover, sources of agricultural information such as extension services, mass media, and farmers’ own efforts have a direct linkage with the accessibility to agricultural information. The study recommends that efforts to increase farmers’ access to agricultural information should be improved. There is a need of improving extension services so as to reach and benefit women farmers. Vugiri ward is located in the highlands that are vulnerable to soil erosion which contributed to poor crop production, hence efforts should be made to introduce soil management practices so as to arrest the situation and increase crop production.